1990
DOI: 10.1111/j.1528-1157.1990.tb05852.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vagal Stimulation on Experimentally Induced Seizures in Rats

Abstract: Repetitive stimulation of the vagus nerve inhibits chemically induced seizures in dogs. We report here the results and conclusions from studies designed to answer some of the immediate questions raised by this finding. (1) Maximal stimulation of vagal C fibers at frequencies greater than 4 Hz prevents or reduces chemically and electrically induced seizures in young male rats. (2) Antiepileptic potency is directly related to the fraction of vagal C fibers stimulated. (3) Vagal stimulation shortens but does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
208
5
13

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(231 citation statements)
references
References 13 publications
5
208
5
13
Order By: Relevance
“…Also, most of these studies were carried out using anesthetized animals and stimulation protocols with higher frequencies and duty cycles than the protocols used clinically and in the present study. Anesthesia also lowers activation of C fibers by VNS (Woodbury and Woodbury, 1990). Consequently, the effects reported in these earlier studies using anesthetized preparations may be distinct from those in unanesthetized animals.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Also, most of these studies were carried out using anesthetized animals and stimulation protocols with higher frequencies and duty cycles than the protocols used clinically and in the present study. Anesthesia also lowers activation of C fibers by VNS (Woodbury and Woodbury, 1990). Consequently, the effects reported in these earlier studies using anesthetized preparations may be distinct from those in unanesthetized animals.…”
Section: Discussionmentioning
confidence: 48%
“…Anesthesia can increase Fos protein throughout brain (Takayama et al, 1994), which could mask effects of vagal stimulation. Anesthesia can also change the threshold for activation of different types of fibers in the vagal bundle (Woodbury and Woodbury, 1990). Further, in all but one study (Naritoku et al, 1995), stimulation of the vagus was carried out using either electrodes or stimulation parameters that resulted in alterations of peripheral autonomic function, (eg mean arterial pressure, MAP; heart rate, HR; and/or respiratory frequency, RF).…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios en animales no han servido únicamente para investigar el mecanismo de acción y valorar la actividad antiepiléptica, también han resultado útiles para determinar la máxima intensidad y parámetros de estimulación sin producir daño químico o eléctrico 80 . Esto es importante porque los parámetros eléctricos constituyen una variable fundamental relacionada con el control de las crisis y otros aspectos fisiológicos 40 .…”
Section: Figura 5 Instantánea Quirúrgica Del Electrodo Tunelizado Y unclassified
“…25 However, this finding was called into question by the observation that the clinical efficacy of VNS in humans was maintained at stimulation parameters thought not to exceed the threshold necessary for C fiber activation. 26 A subsequent study in rats observed that the VNS-induced seizure suppression remained intact, despite selective destruction of C fibers with capsaicin.…”
Section: Rationale and Proposed Mechanisms Of Vns In Epilepsy Controlmentioning
confidence: 99%